The Effect of IFRS on Net Profit And Nominal, Issued And Paid-Up Capital: Evidence From German Listed Companies - Bnar Kareem Darwish (Eurasian Journal of Management & Social Sciences)
The purpose of the study is to examine the financial statements of German publicly traded companies as International Financial Reporting Standards (IFRS) are mandatory. The study relied on the generalized least squares used to calculate the data model to compare the structural errors in the relationship between the income statement and balance sheet items using data from the 30 largest listed companies on the German Market Index (DAX30) between 1994 and 2010. It found that changes in profits due to the adoption of IFRSs do not depend only on net profit and nominal, issued and paid-up capital. The findings indicate that all of the investigated relationships between balance sheet and income statement components have altered considerably. The study concludes that the old profit & loss statement with significant explanatory power disappeared after IFRS adoption. The results reveal considerable improvements in these relations, although their severity and impact vary according to the balance sheet. The data selection creates a size bias that should be considered when extrapolating the findings to other publicly traded firms. This work is the first to use a mandatory, local, accounting, and panel data system to calculate the effect of IFRS adoption using German listed companies.